Study of Iraqi Spinach Leaves (Phytochemical and Protective Effects Against methotrexate-Induced hepatotoxicity in rats) - K. Abdul-Wahab, Farah; Z. Abdul Jalil, Thukaa (Iraqi Journal of Pharmaceutical Sciences, 2017)
Spinach, Spinacia oleracea L is a popular vegetable belonging to the family Chenopodiaceae. This study was concerned with extraction of compounds in Iraqi spinach leaves, preliminary phytochemical evaluation, identification of two biological important flavonols, quercetin and kaempferol in spinach leaves and evaluation of the protective effect of aqueous spinach extract on methotrexate (MTX) induced hepatotoxicity in rats. The percentage yield of extraction procedure, identification of spinach by chemical tests and identification of flavonols by thin layer chromatography (TLC) and High performance liquid chromatography (HPLC) were fully described in this study. The results indicate that the percentage of quarcetin in spinach leaves is more than the percentage of kaempferol in the same plant. The rats were divided into three groups as control, MTX group following a single dose of MTX (20 mg/kg, i.p) saline was administered for 5 days and the MTX+aqueous spinach extract group were rats received 200mg/kg orally of aqueous spinach extract 7days before and 5 days after MTX treatment. MTX administration increased the MDA and decreased GSH, ALP while these changes were reversed in aqueous spinach extract treated group. Histological changes observed in MTX treated group was improved by aqueous spinach extract treatment. The protective effect of aqueous spinach extract against MTX- induced hepatotoxicity could be attributed to the combined effects of its constituents. Key words: Spinach, Kaempherol , Quercetin , Methotrexate, Oxidative stress.